Designing the South African Higher Education System for Student Success (Journal of Student Affairs in Africa, 2021)
South Africa’s higher education system is falling far short of producing the mix of competent graduates to meet the country’s need for social and economic development. The problem of poor patterns of student success is longstanding, and is persisting despite the policy changes and many educationallysound interventions that have taken place in recent decades. This points to entrenched underlying obstacles, including but going beyond the legacy of apartheid, and indicates that they will not yield to supplementary or ad hoc improvement initiatives, however well-conceived individually. This paper is thus based on the proposition that there is a pressing need to design the South African university education system to focus unequivocally on student success and equity of outcomes. This implies,intentionally, that the current system is not designed around any clear commitment to student success. Correcting this must involve a re-prioritisation of goals in the higher education sector, aimed at ensuring that student success is accepted as the end goal of the educational mission of higher education. The paper argues that, if this is to be achieved, what is required is a sophisticated, realistic, coherentand comprehensive strategy for positive change. Given the nature of the higher education system, such a strategy must involve not only a clear vision of the scope of the changes and interventions needed to make a real difference to the performance patterns – in terms of equity as well as overall outcomes – butalso an in-depth understanding of the responsibilities that must be taken by the key stakeholders and the underlying obstacles that must be addressed.The paper offers an outline of the major points of the argument, including the importance of applying design principles to any comprehensive response to the need to place student success at the heart of the higher education agenda.
Keywords: student success; skills shortages; higher education policy; educational development; academic development; curriculum reform; teaching and learning approaches; student support; equity; systemic change; strategy for change; design for learning